Activities to foster the use of hedging by English Language students - Garciga Fernández, Rocío; Mercedo Torna, Nail; Rodríguez Ruiz, Mayra (My University, 2020)
Introduction: In today’s interconnected world, academic writing plays a crucial role since it allows professionals and scientists to disseminate their research and findings in their fields. Academic writing exhibits six main features: it is complex, formal, objective, explicit, hedged, and responsible. Hedges are linguistic devices which writers use to present statements with accuracy and caution, without commitment, and protecting themselves from the audience’s criticism. Despite its confirmed importance, hedging has received less attention leading to the lack of knowledge about this linguistic resource and its inadequate use. Students of the course English Language with a Second Foreign Language (French) at Universidad Central “Marta Abreu” de Las Villas are faced with this problem since they have not received enough training about how to hedge in academic writing. Objetive: propose a set of activities to help these students to properly hedge in academic writing. Theoretical, empirical and statistical methods were used in the study.

En el actual mundo interconectado, la escritura académica tiene un papel crucial pues permite a profesionales y científicos difundir sus investigaciones y resultados. La escritura académica se caracteriza por ser compleja, formal, objetiva, explícita, atenuada y responsable. La atenuación retórica es un recurso lingüístico para presentar las ideas con precisión y precaución, sin compromiso y protegiéndose de las críticas de los lectores. A pesar de su importancia confirmada, ha recibido poca atención, lo que ha contribuido al desconocimiento sobre su uso adecuado. Los estudiantes de la carrera de Lengua Inglesa conSegunda Lengua Extranjera (francés) en la Universidad Central "Marta Abreu" de Las Villas presentan este problema pues no han recibido suficiente preparación acerca de la atenuación retórica
Actividades para potenciar el uso de la atenuación retórica por estudiantes de Lengua Inglesa
Keywords: Academic Writing; Categories of Hedging; Hedging; Writing; Lengua Inglesa; Universidad Central "Marta Abreu" de Las Villas